A Review of Research on Longitudinal Control of Intelligent Vehicles Based on Drive/Brake by Wire - Peicheng Shi; Xinyu Qian; Chakir Chadia; Yu Sun; Taonian Liang; Aixi Yang (World Electric Vehicle Journal)
In recent years, with the rapid innovation of science and technology, wire control technology, as a key technology, has achieved the transmission control of vehicles through the form of “electrical signals”, which has become an important foundation for realizing the high degree of intelligence of vehicles. This paper provides a comprehensive overview of the wire control technology, its application and longitudinal control strategy, and focuses on the longitudinal control technology of intelligent vehicles based on drive/brake by wire. The specific content includes five parts: first, the principles and characteristics of wire control technology and its application in intelligent vehicles are introduced; then, two commonly used longitudinal control strategies are described; then, the application of classical control technologies (such as PID, MPC, and sliding-mode control) in the longitudinal control of intelligent vehicles is discussed, including their working principles, characteristics and related research; subsequently, the AI control technology (deep reinforcement learning) is presented in the longitudinal control of intelligent vehicles, discussing its theoretical basis, the current status of algorithm research, control methods, and practical applications, etc.; finally, the paper summarizes the advantages and disadvantages of the classical control technology and AI control technology, and looks forward to the application and development prospects of these two control technologies in the control of intelligent vehicles.